Effect of Indonesian elderly exercise to muscles flexibility in Posyandu Lansia RW XV Gendingan, Jebres, Surakarta - Stefanus Bramantyo Widigdo; Desy Kurniawati Tandiyo; Lilik Wijayanti (Nexus Kedokteran Klinik, 2015)
Background : Motion limitation usually found as a result of the decreased flexibility of muscles in elderly. The decreasing flexibility might be prevented by doing physical activities. For elderly, the recommended physical activity was Indonesian elderly exercise. This studys aim was to understand the effect of Indonesian elderly exercise to increase muscles flexibility in elderly. Methods : This study was a quasi-experiment using pre and post-test without control design method, which held on September-October 2014 in Posyandu Lansia RW XV Gendingan, Jebres, Surakarta. Sampling method was using purposive sampling, with inclusion and exclusion criteria. Data measured with chair-sit and reach test. Thirty subjects analyzed with marginal homogeneity test. Result : This study showed significant effect of Indonesian elderly exercise in increasing muscle flexibility of elderly. The marginal homogeneity test was p = 0.000 (< 0.05). Conclusion : There was significant effect from Indonesian elderly exercise in increasing muscle flexibility of elderly. Key Words : Elderly, Muscle Flexibility, Indonesian Elderly Exercise.